ANALISIS PREDIKSI POTENSI KEBANGKRUTAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA DHARMA CURUP KABUPATEN REJANG LEBONG - Deni Veriadi (Politeknik Raflesia Press, 2018)
This research aim to to know Company potencial bankruptcy to Area PDAM Tirta DharmaCurup Sub Province of Rejang Lebong. Analysis method which used in this research l ofAltman Z-Score Methode. representing analyzer used for the prediction of bankruptcy ancompany. The data used are secondary data obtained of financial statement of PDAM TirtaDharma Curup Year 2012 - 2016. Result of Analysis indicate that value of Altman Z-Score toPDAM Tirta Dharma Curup, Year 2012 - 2016 of Period residing in zone determinant (Z) <1,81 indication condition of that PDAM Tirta Dharma Curup find company's financialdistressto finance performance and company in a bankruptcy condition. Result of the AltmanZ-Score also indicate that PDAM Tirta Dharma Curup represent company which dont Likuidand dont not solvable or equally cannot guarantee and fulfill leabilities short debt and also islong debt.